The role of APC/C in cell cycle dynamics, growth and development in cereal crops - de Oliveira, Perla Novais; da Silva, Luís Felipe Correa; Eloy, Nubia Barbosa (Frontiers in Plant Science, 2022)
Cereal crops can be considered the basis of human civilization. Thus, it is not surprising that these crops are grown in larger quantities worldwide than any other food supply and provide more energy to humankind than any other provision. Additionally, attempts to harness biomass consumption continue to increase to meet human energy needs. The high pressures for energy will determine the demand for crop plants as resources for biofuel, heat, and electricity. Thus, the search for plant traits associated with genetic increases in yield is mandatory. In multicellular organisms, including plants, growth and development are driven by cell division. These processes require a sequence of intricated events that are carried out by various protein complexes and molecules that act punctually throughout the cycle. Temporal controlled degradation of key cell division proteins ensures a correct onset of the different cell cycle phases and exit from the cell division program. Considering the cell cycle, the Anaphase-Promoting Complex/Cyclosome (APC/C) is an important conserved multi-subunit ubiquitin ligase, marking targets for degradation by the 26S proteasome. Studies on plant APC/C subunits and activators, mainly in the model plant Arabidopsis, revealed that they play a pivotal role in several developmental processes during growth. However, little is known about the role of APC/C in cereal crops. Here, we discuss current understanding of the APC/C controlling cereal crop development.